The influence of brand experience and service quality to customer loyalty mediated by customer satisfaction in Starbucks coffee Malang - Devia, Aldeline Nolita; Aisjah, Siti; Puspaningrum, Astrid (MEC-J (Management and Economics Journal), 2018)
Â This study discusses the effect of Brand Experience and service quality on customer loyalty mediated customer satisfaction. The purpose of this study was to determine and analyze in depth the effect of brand experience and service quality on customer loyalty mediated customer satisfaction at Starbucks Coffee Malang. This research uses explanatory research that explain the causal relationship between the variables studied.By using a survey of 180 respondents to test the research hypothesis.Research data analysis using the test instrument, the classical assumption test, multiple linear regression, and path analysis / Path Analysis. The test results prove the instrument has met the criteria of validity and reliability, the classic assumption test results also have met the criterion of the assumptions of normality, autocorrelation, Non-Multicolinearity and heterocedastisity. In this study obtained; a). Brand experience on consumer satisfaction with the value of 0.309, or 30.9%, b). The quality of service to customer satisfaction with the value of 0.387 or 38.7%., C). Brand experience on consumer loyalty to the value of 0.216 or 21.6%., D). Service quality on customer loyalty with a value of 0,305 or 30.5%., E). Effect of brand experience and service quality customer satisfaction with the value of 0.581 or 58.1%., F). Effect of brand experience and service quality on customer loyalty with a value of 0.657 or 65.7%., G). Effect of brand experience and service quality on customer loyalty mediated consumer satisfaction with the value of 0.438 or 43.8%. Based on these results, it is necessary to enhance the consumer's commitment to give satisfaction to the consumers better by excellent service or "service excellence" is the attitude and serve with satisfactory manner from the present level while maintaining the brand experience Starbucks Coffee Malang.Â